Polska Kronika Filmowa w latach 1945–1968 jako medium partyjne. Zarys problemu - Jędrzejski, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The inspiration for this sketch was the analysis of documents produced by the party and state authorities, and state and party leaders of the Polish People's Republic, with reference to the activities at that time of an important channel of communication: the Polish Film Chronicle
Polish Film Chronicle in the years 1945–1968 as a medium party. Outline of the problem
Keywords: Polish Film Chronicle; Olga Borzechowa; Jerzy Bossak